The comparison of production ability of naked and husked oats - Moudrý, Jan; Sterba, Zdenek; Moudrý Jr., Jan; Bárta, Jan (MTT, 2004)
The aim of the research work was to assess differences in yield formation of naked and husked oats and to determine the affecting factors. The exact field small-plot experiments with three naked oats varieties (Abel, Izak, and Salomon) and with three husked oats varieties (Auron, Edmund, and Expander) were carried out in two Austrian sites (Lambach and Freistadt) and in two Czech sites (Èeské Budìjovice and Humpolec) during 1999-2001. There were determined mainly panicle length (LP), number of whorls (NW), number of branches (NB), number of spikelets (NS), number of grains (NG) and weight of grains per panicle (WG). Mean values of harvest index for husked and naked oats were 45.8 and 39.7 %, respectively, with negative relationship with plant height and in a positive relationship with WG. The husked varieties reached higher mean levels of the all yield components. The stands of the husked varieties had higher harvest densities, panicles per m2, gains per m2 and minimum variability of the coefficient of productive tillering. The weight of panicles was affected by number of grains, rather than their weight. Yield variability has been influenced in greater extent by number of formed spikelets than by their productivity as reported by Peltonen-Sainio (1994). The yield was affected not only by the higher panicle productivity, but also by the stand density. The inter-year variability of the panicle productivity was influenced mainly by precipitation rate during the period of spikelets differentiation and grain filling. The effect of genotype on the panicle productivity was 15.5 %. Crude grain yields in our experiments were 5.83 and 4.30 t/ha for husked and naked oats, respectively. The tested naked varieties would produce at the observed output the yield of oats rice 4.20 and 4.26 t/ha. However, such high output of husked oats has not been reached in farming practice. Stelzner (1990) reported outputs 46-55 and 86-92.4 % for husked and naked oats, respectively, under German conditions. In our experiments, the production of dehulled grains was 3.21 and 3.83 t/ha at the outputs 55 and 89 % for husked and naked oats, respectively. The oats rice production was observed to be for 31.3 % higher in the naked varieties as compared to the husked ones. Such results support the interest in breeding and cultivation of naked oats under the conditions of the Czech Republic. Burrows, V. D., et al.2001. Canadian Journal of Plant Science 81:727-729; Peltonen-Sainio, P. 1994.
Keywords: Ka; hulled oat; naked oat; yield; panicle productivity